The monotypic brazilian genus Diacrodon is a synonym of Borreria (Spermacoceae, Rubiaceae) : morphological and molecular evidences - Miguel, Laila Mabel (2018)
Fil: Miguel, Laila Mabel. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Botánica del Nordeste; Argentina.